Demographic indicators of dogs and cats with owner in the district of Lince, Lima-Peru, 2020 - Castillo, Geraldine (2022)
The aim of the study was to describe the demographic indicators of the population of dogs and cats with owner in the district of Lince, Lima. The study was based on the use of surveys. The study population was the dwellings of five sectors of the Lince district. The study collected a total of 737 valid surveys, which came mainly from houses (60.5%) and apartments (37.3%). The results show that 46.0% of the houses had dogs and 16.4% had cats. The average number of animals per dwelling was 1.4 for dogs and 1.8 for cats. The human: dog ratio was 5.4, and the human: cat ratio was 12.3. The percentage of survival of their offspring was 84% in dogs and 81.8% in cats and estimated life expectancy was 11.5 and 5.8 years, for domestic dogs and cats, respectively. Among dogs, there was a prevalence of male (53.6%), small size (49.4%), undefined breed (50.6%), non-sterilized (61.2%), and age average of 5.3 years. Among cats, there was predominance of females (57%), sterilized (69.1%), undefined breed (90.3%) and age average of 4.1 years. It is expected that the information presented in the research can contribute to the competent authorities in relation to the management and policies of responsible pet ownership in the specific sector of study.